PERSEPSI GURU KELAS TERHADAP ANAK BERKEBUTUHAN KHUSUS DI SD PAYAKUMBUH - Desi - Kurniawati (Jurnal Penelitian Pendidikan Khusus, 2014)
The background of this study was the difference in perception or perspective teachers of children with special needs in elementary school Payakumbuh . The purpose of this research is to gain an overview of classroom teachers 'perceptions of children with special needs include classroom teachers' understanding of children with special needs , where children with special needs in schools , social interaction with children with special needs teachers , children with special needs social interaction with peers , and achievement studied children with special needs . The methodology in this research is descriptive quantitative approach . The sampling technique is the total sampling totaling 34 classroom teachers who are in school 5 Inclusion in the District of North Payakumbuh Payakumbuh . The technique of collecting data through a questionnaire using Likert scale and Guttman scales . Total number of question items were 53 items relating to how perceptions of classroom teachers of children with special needs . The collected data were analyzed using statistical formula percentage . The result showed 50.7 % of teachers understand overview of children with special needs , 58.2 % of teachers noticed the presence of children with special needs in schools , 58.8 % of children with special needs social interaction with teachers , 53.4 % of children with special needs do social interaction with peers , and 40.8 % of children experience a disruption in learning achievement . It can be concluded low achievement children with special needs in the learning process . It is suggested to teachers to pay more attention to children with special needs learn in the classroom and outside the classroom , in order to increase children's achievement and socialization of children do not have a problem .